Systematic review and network meta-analysis of the efficacy and safety of lidocaine 700 mg medicated plaster vs. pregabalin. (2nd January 2020) - Buksnys, Titas; Armstrong, Nigel; Worthy, Gill; Sabatschus, Ingo; Boesl, Irmgard; Buchheister, Bettina; Swift, Stephanie L.; Noake, Caro; Huertas Carrera, Vanessa; Ryder, Steve; Shah, Dhwani; Liedgens, Hiltrud; et al.
Abstract: Objective: Neuropathic pain prevalence is estimated between 7% and 10% of the population. International guidelines recommend a variety of drugs at different therapy lines for pain relief. However, side effect profiles, for example, prompted the UK government recently to classify pregabalin and gabapentin as class C drugs. Lidocaine 700 mg medicated plaster (LMP) might be a safer alternative. A systematic review assessed how LMP and pregabalin compared in terms of efficacy and safety. The review focused on pain reduction, quality of life and adverse events in peripheral neuropathic pain (PNP) i.e. post-herpetic neuralgia, diabetic peripheral neuropathy, post-surgical/trauma, or other PNP conditions. Methods: Electronic databases were searched as well as a number of other sources up to November 2018. Sensitive strategies were used, with no restriction by language or publication status. Two independent reviewers screened records and extracted data with consensus determining final decisions. Risk of bias was assessed using the Cochrane Collaboration 2011 checklist for RCTs. Full network meta-analysis was conducted to compare LMP to pregabalin 300/600 mg in terms of pain reduction, quality of life, as well as serious adverse events and selected adverse events. Trials with enriched enrolment design were excluded. Results: Searches retrieved 7, 104 records. In total 111 references pertaining to 43 RCTs were included for data extraction. Bayesian network meta-analysis of several pain outcomes showed no clear difference in efficacy between treatments However, LMP was clearly advantageous in terms of dizziness and any adverse event vs. pregabalin 600 mg/day and discontinuations vs. pregabalin 300 mg/day or 600 mg/day, as well as being associated with improved quality of life (albeit in this case based on weak evidence). Conclusions: LMP was found to be similar to pregabalin in reducing pain in all populations but had a better adverse events profile.